Relationship of Compensation, Training and Work Environment to Employee Motivation - Ade Ary Machmud; Mahlia Muis; Muhammad Yunus Amar (Magister Management, Hasanuddin University, 2021)
Company performance comes from employee performance. One of the ways to drive up employee performance is motivation. This study aims to examine the relationship between compensation, training, and work environment on employee work motivation at CV. Amanda Brownies, one of the popular food processing companies in Makassar, South Sulawesi Province. The approach taken is a quantitative approach with multiple linear regression methods. To conduct the research, the study collected data from 60 employees of the company as respondents using a questionnaire of a five-Liker scale. Based on the research model developed, the data is then analyzed using multiple regression analysis. The result of the study found that the work environment has a significant effect on employee motivation. However, interestingly, the results of the study indicated that compensation and training do not have a significant effect on motivation. The work environment has a significant effect on employee motivation.